Quantitative Proteomic and Network Analysis of Differentially Expressed Proteins in PBMC of Friedreich’s Ataxia (FRDA) Patients - Pathak, Deepti; Srivastava, Achal Kumar; Padma, M. V.; Gulati, Sheffali; Rajeswari, Moganty R. (Frontiers in Neuroscience, 2019)
Friedreich's ataxia (FRDA), a neurodegenerative disorder caused by (GAA) triplet expansion in the FXN gene, resulting in reduced expression of the mitochondrial protein, frataxin. Given the ongoing drug trials, identification of reliable and easily accessible biomarkers for monitoring disease progression and therapeutic intervention is a foremost requirement. In this study, comparative proteomic profiling of PBMC proteins from FRDA patients and age and gender-matched healthy controls was done using 2D-Differential in-Gel Electrophoresis (2D-DIGE). Protein-protein Interaction (PPI) was analyzed using BioGRID and STRING pathway analysis tools. Using biological variance analysis (BVA) and LC/MS, we found eight differentially expressed proteins with fold change ≥ 1.5; p ≤ 0.05. Based on their cellular function, the identified proteins showed strong pathological role in n neuroinflammation, cardiomyopathy, compromised glucose metabolism and Iron transport which are the major clinical manifestations of FRDA. Protein-protein network analysis of differentially expressed proteins with frataxin further supports their involvement in the pathophysiology of FRDA. Considering their crucial role in the cardiac and neurological complications respectively, the two down-regulated proteins, actin α cardiac muscle 1(ACTC1) and pyruvate dehydrogenase E1 component subunit β(PDHE1)are suggested as potential prognostic markers for FRDA